2012
DOI: 10.7156/v5i3p148
|View full text |Cite
|
Sign up to set email alerts
|

Weekly Biological Variability of Urinary Organic Acids

Abstract: Use of LC-MS/MS methods has improved sample preparation and increased throughput for the measurement of 40 or more organic acids in urine. In order to assess the significance of abnormalities that might be attributed to nutritional inadequacies or other metabolic disturbances, the week-to-week variation of results due to normal physiological responses needs to be established. This study determined the biological variability for 37 organic acids plus hippuric acid, D-arabinitol and 8-hydroxy-2'deoxyguanosine in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Pyroglutamic acid (PGA or 5‐oxoproline) was measured in urine specimens submitted once weekly for 8 weeks by 22 subjects as part of an IRB‐approved study to determine biological variability in a profile of organic acids (Lord et al. ). The between‐run analytical variability for pyroglutamate was 3.5% at 50.9 μg/g creatinine, a value anomalously different from its calculated overall biological variability (CV b ) of 33.5%, indicating that something other than analytical variability was contributing to the observed patterns.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Pyroglutamic acid (PGA or 5‐oxoproline) was measured in urine specimens submitted once weekly for 8 weeks by 22 subjects as part of an IRB‐approved study to determine biological variability in a profile of organic acids (Lord et al. ). The between‐run analytical variability for pyroglutamate was 3.5% at 50.9 μg/g creatinine, a value anomalously different from its calculated overall biological variability (CV b ) of 33.5%, indicating that something other than analytical variability was contributing to the observed patterns.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Indeed, we observed that cord serum and placental 3-OHB were positively associated with cord serum and placental 2-hydroxybutyrate (2-OHB) and 2-aminobutyrate, biomarkers of glutathione synthesis and status. 42,43 Cord serum 3-OHB was also negatively associated with pyroglutamate, a metabolite related to glutathione depletion 44,45 and positively associated with placental glutathione concentrations. 3-OHB acts as a signaling molecule to protect against oxidative stress through several proposed mechanisms, including activation of antioxidant response-related transcription factors.…”
Section: Discussionmentioning
confidence: 99%
“…Under conditions of oxidative stress, glutathione biosynthesis increases, and cysteine may become limiting. Thus, as a by-product of cysteine production through glutamate-cysteine ligase, 2-hydroxybutyrate is a sign of glutathione synthesis and oxidative stress [85]. DEHP has been shown to reduce glutathione concentrations in mouse kidneys through the depletion of transcription factor nuclear factor erythroid 2-related factor 2 (Nrf2) and glutamate-cysteine ligase abundance [86].…”
Section: Associations With Phthalate Exposurementioning
confidence: 99%